Cation-induced ring-opening and oxidation reaction of photoreluctant spirooxazine–quinolizinium conjugates - Pithan, Phil M (Beilstein J Org Chem, 2020)
Two new spiroindolinonaphthoxazine derivatives with an electron-accepting styrylquinolizinium or styrylcoralyne unit, respectively, were synthesized, and the influence of such an arylvinyl substituent on the chemical and photochemical properties of the compounds was investigated. Specifically, these spirooxazines turned out to be resistant towards the photoinduced merocyanine formation, and the irradiation with light mainly led to photodegradation of the substrates. However, it was shown by colorimetric and fluorimetric screening assays as well as by detailed NMR spectroscopic and mass spectrometric studies that the addition of particular metal ions (Cu(2+), Fe(3+), and to a certain extent Hg(2+)) initially induced a ring-opening reaction that was irreversibly followed by a fast ring closure–deprotonation–oxidation sequence to give styryl-substituted naphthoxazole derivatives as the products quantitatively. For the quinolizinium-substituted spirooxazine derivative, the formation of the respective oxidation product caused the development of a broad absorption band between 425 nm and 500 nm and a new emission band at λ(fl) = 628 nm, so that it may be employed as a selective chemosensor or chemodosimeter for the colorimetric and fluorimetric detection of Cu(2+) and Fe(3+).